New Isotopes for the Treatment of Pancreatic Cancer in Collaboration With CERN: A Mini Review - Burkhardt, Claudia; Bühler, Léo; Viertl, David; Stora, Thierry (Frontiers in Medicine, 2021)
The use of radioactivity in medicine has been developed over a century. The discovery of radioisotopes and their interactions with living cells and tissue has led to the emergence of new diagnostic and therapeutic modalities. The CERN-MEDICIS infrastructure, recently inaugurated at the European Centre for Nuclear Research (CERN), provides a wide range of radioisotopes of interest for diagnosis and treatment in oncology. Our objective is to draw attention to the progress made in nuclear medicine in collaboration with CERN and potential future applications, in particular for the treatment of aggressive tumors such as pancreatic adenocarcinoma, through an extensive review of literature. 55 out of 208 articles, published between 1997 and 2020, were selected based on relevancy. Meetings were held with a multi-disciplinary team, including specialists in physics, biological engineering, chemistry, oncology and surgery, all actively involved in the CERN-MEDICIS project. In summary, new diagnostic and therapeutic modalities are emerging for the treatment of pancreatic adenocarcinoma. Targeted radiotherapy or brachytherapy could be combined with existing therapies to improve the quality of life and survival of these patients. Many studies are still in the pre-clinical stage but open new paths for patients with poor prognosis.